Nasionalisme dalam Rindu; Telaah Terhadap Puisi “Lianni Gharib” Karya Badar Syakir Sayyab: Nationalism in Longing; Study of the poem Lianni Gharib by Badar Syakir Sayyab - Syifa Ramadhanti; Ahfa Rahman Syah; Mawardi Mawardi; Lilis Malikatus Sakinah; Ika Amrikhanifah (Information Technology and Science(ITScience), 2025)
Nationalism is often raised in Arabic poetry, presented in various forms, to foster a spirit of change in current social dynamics. In this case, the Iraqi poem